Manufacture of wood processor from unsaturated polyester foam and walnut husk waste - Waleed Bdaiwi, Falah Dawood, (Design Engineering, 2021)
A polymeric adhesive made of unsaturated polyester resin was used in the recycling of walnut husk waste for the purpose of manufacturing a wooden furniture processor (0, 2.5, 5, 7.5, 10, 12.5, 15)% and with a grain size (45) μm of walnut shell granules, tests were conducted to study some mechanical properties (tensile, bending, shock, hardness) and thermal conductivity in addition to the surface morphology of all samples.The results of the tests showed an improvement in the mechanical properties, and these properties were enhanced with an increase in the weight fraction of the walnut husk granules. The results also showed a decrease in the thermal conductivity with an increase in the weight fraction of the reinforcement material.